Analysis of Return to Sport and Weight Training After Repair of the Pectoralis Major Tendon. Issue 9 (July 2019) - Liu, Joseph N.; Gowd, Anirudh K.; Garcia, Grant H.; Manderle, Brandon J.; Beletsky, Alexander; Nicholson, Gregory P.; Forsythe, Brian; Romeo, Anthony A.; Verma, Nikhil N.
Background: The use of routine patient-reported outcomes after repair of the pectoralis major tendon (PMT) is often prone to the ceiling effect owing to the high functional demand of those who sustain this injury. Hypothesis: A significant number of patients are expected to fail to achieve return to preoperative activity after PMT repair despite achieving significant improvements in functional score. Study Design: Case series; Level of evidence, 4. Methods: A prospectively maintained institutional database was reviewed for all patients undergoing PMT repair from 2010 to 2016. Patients were surveyed with regard to pre- and postoperative participation in sports, level of intensity, maximum weight repetitions in exercises utilizing the PMT, and American Shoulder and Elbow Surgeons (ASES) and Single Assessment Numeric Evaluation (SANE) scores. Results: Forty-four patients (73.3%) were available for final follow-up. All patients were male. Mean ± SD follow-up was 51.1 ± 24.1 months. Mean age was 39.6 ± 8.8 years (range, 24-61 years), and mean body mass index was 28.6 ± 3.5 kg/m 2 . The dominant side was affected in 20 of 44 cases. Acute repairs were performed in 30 cases and chronic in 14. There were statistically significant improvements in both ASES and SANE scores ( P < .001). Return to sport at any level was achieved by 43 of 44 (97.7%) patients, while 22 of 44 patients (50.0%) reported returning to sport at the same or better intensity as preinjury status. On average, there was a 23.3% ± 45.6% decrease in 1–repetition maximum (1RM) barbell bench press, 14.7% ± 62.3% decrease in 5–repetition maximum barbell bench press, 24.3% ± 21.8% decrease in 1RM dumbbell bench press, 35.7% ± 32.1% decrease in 1RM dumbbell fly, and 15.6% ± 39.8% decrease in consecutive push-ups able to be performed. Seventeen patients (38.6%) reported a degree of apprehension that affected their ability to lift weights. When all preoperative variables were accounted for, history of surgery to the contralateral shoulder (odds ratio, 0.600; 95% CI, 0.389-0.925) was associated with a decreased likelihood of returning to sport at the same or better level of intensity, while injury sustained during sport had a greater likelihood (odds ratio, 2.231; 95% CI, 1.234-4.031). Conclusion: Patients undergoing PMT repair should expect significant functional improvements and a low complication rate. Yet, only 50% are able to return to preoperative intensity of sport, and they will also have significant reductions in their ability to weight lift.